The effects of gold nanoparticles with different surface coatings and sizes on biochemical parameters in mice - Özçiçek, İlyas; Çakıcı, Çağrı; Ayşit, Neşe; Erim, Ümit Can (The European Research Journal, 2023)
Objectives: Gold nanoparticles are very popular metallic nanomaterials and they have a wide spectrum of biomedical applications. This study was aimed to the production of stable and monodisperse polyethyleneimine (PEI) and polyethylene glycol (PEG) coated gold nanoparticles (AuNP20 and AuNP50), investigation of their in vivo biochemical effects in the BALB/c mice. Methods: Gold nanoparticles were synthesized and their surfaces were modified by PEI and PEG. All the necessary physicochemical characterizations were performed. After the single high dose i.v. injection (5 mg Au/kg animal weight) of the AuNP groups, their in vivo biochemical effects were evaluated multiparametrically in the mice on day 14. Results: Highly monodisperse and stable AuNPs were synthesized successfully. Significant changes in the biochemical hemogram parameters were observed depending on the surface coatings of the AuNPs. PEI and PEG surface coatings increased biocompatibility. No excessive oxidative stress response was observed in all the gold nanoparticle groups. Conclusions: It has been concluded that the surface chemistry of the particles is a more decisive parameter than the size in terms of in vivo biochemical toxicity. The surface functionalization, stability and biocompatibility of the AuNPs are important parameters for the potential biomedical applications of gold nanoparticles in future studies.